Erratum to: Dosimetry on first clinical dark-field chest radiography (Medical Physics, (2021), 48, 10, (6152-6159), 10.1002/mp.15132) - Frank, Manuela; Urban, Theresa; Willer, Konstantin; Noichl, Wolfgang; De Marco, Fabio; Schick, Rafael; Gleich, Bernhard; Schegerer, Alexander; Lechel, Ursula; Meyer, Pascal; Mohr, Juergen; Koehler, Thomas; et al. (Medical Physics, 2022)
In our work, we evaluated the effective dose values for first clinical dark-field chest radiography, both for examinations of the reference person and a certain patient collective consisting of 92 patients. Unfortunately, the histogram in Figure 4 consists of more patients than introduced in the running text, as more of the participants in the ongoing studies were mistakenly included. In the published Figure 4, instead of data points of 92 patients, data points of additional patients are included. This changes the mean value, as indicated by a dashed line, from 38.7 μGy (correct value as given in Figure legend and running text) to 41.1 μGy (as depicted in published Figure 4). The corrected version can be found in the attached Figure 1. Figure legend is not subject to change. Please note that this does not change the message of the paper. All dose values in the running text and figure legends are correct. The reported effective dose value for the reference person is correct. The reported effective dose values for the first 92 patients are correct. Even by including more patients, the recorded mean value is below the reference value, therefore we fulfill the legal requirements regarding the local diagnostic reference level (DRL).
CRIS-Team Scopus Importer:2023-03-08